Public school development and planning: parents 19 criteria of selecting public school in Gombak district - Mohd Ibrahim, Nuraihan; Mohamed Osman, Mariana; Bachok, Syahriah (Elsevier, 2014)
School is a nucleus of the society. School development should be planned based on the sustainable concept. People need education for future employment and to improve quality of life. The purpose of this paper is to determining parents 19 criteria in selecting the suitable public school for their children. There are various factors underlying in determining the school selection which are location, distance, school facilities, school 19s performance, extracurricular and school environment. Hopefully, the paper will benefit the local authority, parents as well as children in term of public school development in the community.